Conocimientos y prácticas sobre prevención y manejo de enfermedad diarreica aguda, en madres de ninos/as del Centro Infantil del Buen Vivir Pedestal MIES, Loja 2014-2015 - Lima Ontaneda, Gabriela Alexandra (2015)
Acute diarrheal disease (ADD) is a syndrome that is a major health problem in vulnerable groups such as children under five, for its high burden of morbidity and mortality worldwide and nationally. This research entitled Knowledge and practices on prevention and acute diarrheal disease management in mothers of the children of the whose goal was to determine the maternal knowledge and practices on prevention and management of acute diarrheal disease. Descriptive research methodology that involved 64 mothers of children who attend the CIVB is implemented; they collect information by a survey, a technique and as an instrument, in the form of questions. For information processing they used a software called Excel, which was used for the representation of information in tables we are used. The results of this study show that mothers did not know about prevention of acute diarrheal disease as a significant percentage of the study show that a percentage of the group did not know the factors to develop and measures that reduce the risk of producing it; while the highest percentage of mothers known about handling acute diarrheal disease in which symptoms mentioned correctly urgent to take the child / to the health service, the preparation of oral rehydration salts and homemade ORS, signs dehydration and warning signs to prevent complications. In terms of prevention practices Acute Diarrheal Disease is determined that the highest percentage of mothers makes good practice as complementary feeding from six months of age, sewage disposal and sewage cleaning bottle among others. Management practices shows that a large percentage of mothers have good practices as indicated and provide the right kind of fluids after the diarrheal episode, but in a smaller percentage still remains inadequate practices. Keywords: Acute Diarrheal Disease, knowledge, practices, prevention.